Analysing the potential of Wikipedia for science education using automatic organization of knowledge. Issue 4 (7th November 2017) - Figuerola, Carlos G.; Groves, Tamar
Abstract : Purpose: The purpose of this paper is to analyse the presence and structure of scientific content in the Spanish version of Wikipedia by applying social networks analysis techniques. Design/methodology/approach: Wikipedia articles have hyperlinks that connect them, so it is possible to represent Wikipedia as a network, in which the nodes are the articles and the edges are hyperlinks. The authors use communities detection techniques, in order to identify clusters of articles with similar content and then the authors carry out a manual analysis to detect science articles and identify the most representative scientific fields and their main features. Findings: The authors conclude that science articles comprise 11.66 per cent of Spanish Wikipedia articles and that the most important clusters of scientific articles do not always coincide with classical science disciplines. Originality/value: As Wikipedia is an open content resource, which is constructed by a community of users, and is widely employed in educational contexts by both students and teachers, this kind of analysis contributes to understanding Wikipedia better as an educational tool.